Tanjungpura Port as an International Hub Port to Improve Economic Competitiveness: an Overview from International Law - Wiko, Garuda; Kinanti, Fatma Muthia; Syafei, Muhammad; Darajati, Muhammad Rafi; Sudagung, Adityo Darmawan (Indonesian Journal of International Law, 2023)
The Indonesian Government is currently in the process of developing several new ports in its territory as a means of supporting infrastructure development and maritime connectivity. One of them is the Development of the Kijing Terminal Port in the Province of West Kalimantan. It is important to study international and national legal regulations related to ports and how they affect the development of Tanjungpura Port, Kijing Terminal, which will be directed to become one of the international hub ports in Indonesia. The research methodology employed in this study is normative, with in-concreto legal study approach. It is found that, the consequence of the status of the "international hub" is that it is necessary to ensure that the best international port management and regulatory systems can be implemented at Tanjungpura Port, Kijing Terminal. The development plan for the Kijing Terminal Area to support increased regional competitiveness includes the construction of a Bauxite Smelter, the construction of the Kijing Industrial area, the construction of the Kijing Special Economic Zone (SEZ), the construction of a nuclear power plant to meet community and industry needs, the construction of the Pontianak - Sei Pinyuh, Sei Toll Road route Pinyuh – Mempawah, Mempawah – Kijing, Kijing – Singkawang, the construction of the Trans Kalbar Railway Road to increase ease of access and the establishment of the PT EUP refinery in Kijing. Several inputs that need to be considered so that Tanjungpura Port Governance can be carried out efficiently include repositioning the Government's role in the management and development of the Port with a focus on supporting market mechanisms and fair competition. In addition, related parties need to stipulate a Minister of Transportation Regulation on Ship Security Management and Port Facilities to provide a reference regarding the implementation of the ISPS Code or International Provisions for Ship Security and Port Facilities.